Scoundrels to the hoosegow Perry Mason moments and entertaining cases from the files of a prosecuting attorney - Swingle, Morley (University of Missouri Press, 2007)
"Morley Swingle, veteran prosecuting attorney, combines true crime and legal analysis with a healthy dose of humor as he re-creates more than thirty stories of villains, heroes, and ordinary citizens, taking readers from the crime scene to the courtroom and sharing the occasional 'Perry Mason moment'"--Provided by publisher.